Opportunities For Utilization of Plywood Waste in Sustainable Interior Industry - Susanti, Lina; Prasetyo, Angga Dwi; Soares, Balbino da Conceicao; Pudianti, Anna; Sumardiyanto, B. (Journal of Architectural Research and Education, 2026)
The interior industry in Indonesia is experiencing rapid growth, along with the increasing demand for furniture. However, this increase has also led to increase in material waste, particularly multiplex waste, which negatively impacts the environment and contributes to deforestation. This research aims to explore and analyze the utilization of small pieces of multiplex material as derivative products, which can reduce waste and support sustainable support sustainable architectural practices. The research methods usedincluded both quantitative and qualitative approaches with a case study on a multiplex-based interior design project based on multiplex, providing a more in-depth overview of innovative applications of leftover materials. The results showed that optimizing the use of small pieces of multiplex can reduce the residual material from 8.6% to 0.105%, while reducing the demand for raw wood. The implications of this research suggest that the interior industry can adopt more sustainable practices through the development of derivative product development, which not only improves material efficiency but also supports forest conservation and forest conservation and awareness of effective waste management. As such, this research makes a significant contribution to sustainability in the interior industry.